Trust-Based Relational Intervention® (TBRI®) Impact for Traumatized Children-Meaningful Change on Attachment Security and Mental Health after One Year - Monika Misevičė; Lina Gervinskaitė-Paulaitienė; Sigita Lesinskienė; Izabelė Grauslienė (MDPI AG, 2024)
Children from vulnerable backgrounds often have insecure attachment or disorganized attachment, which are related to psychological troubles, and such children need interventions to help them heal. The attachment system reorganizes in middle childhood, and other important adults play a considerable role in children's lives. Thus, it is essential to weigh the impact of psychosocial interventions, while the main focus of the intervention is the staff member's direct work with the child through a trusting relationship. The primary purpose of this study is to investigate whether children's attachment security and mental health outcomes change after participating in a trauma-informed, attachment-based, Trust-Based Relational Intervention (TBRI) provided in a daycare center. It was a case-series study involving twelve children aged 8-11 years. The child attachment interview (CAI), CBCL/6-18, TRF/6-18, and clinical interviews for parents and children were used, measuring the change between the TBRI implementation in the daycare center and after one year. For ten participants, we noticed an improvement in mental health; for seven participants, security scales improved; for two participants, their disorganized attachment changed into insecure-dismissing. We have preliminary evidence that vulnerable children may benefit in terms of attachment security and mental health from the trusting relationship that staff build using the TBRI.